2020
DOI: 10.1111/ajt.15611
|View full text |Cite
|
Sign up to set email alerts
|

Tailored use of belatacept in adolescent kidney transplantation

Abstract: Adolescent transplant recipients are at risk for nonadherence, development of de novo donor‐specific antibody (dnDSA), and allograft loss. Belatacept, a selective T cell costimulatory blocker, is associated with reduced dnDSA, improved renal function, and prolonged allograft survival when compared to calcineurin inhibitor‐based regimens in adults; however, its use in children is scant. Three adolescents were initiated on belatacept between August 2017 and September 2018 at the time of kidney transplantation. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The pediatric study of de novo belatacept use reported 10 mg/kg on postoperative days 1, 4, 14, 28, 56, and 84 followed by 5 mg/kg monthly. 125 The pediatric study on conversion to belatacept used similar dosing. 124 The chief concern with belatacept, as illustrated by the BENEFIT A randomized controlled trial of 42 pediatric low-immunologic risk recipients found no difference in the incidence of acute rejection or graft loss but lower incidence of hypertension and hyperlipidemia with steroid withdrawal vs. steroid-inclusive immunosuppression.…”
Section: Dosing and Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pediatric study of de novo belatacept use reported 10 mg/kg on postoperative days 1, 4, 14, 28, 56, and 84 followed by 5 mg/kg monthly. 125 The pediatric study on conversion to belatacept used similar dosing. 124 The chief concern with belatacept, as illustrated by the BENEFIT A randomized controlled trial of 42 pediatric low-immunologic risk recipients found no difference in the incidence of acute rejection or graft loss but lower incidence of hypertension and hyperlipidemia with steroid withdrawal vs. steroid-inclusive immunosuppression.…”
Section: Dosing and Side Effectsmentioning
confidence: 99%
“…124 A recent retrospective study described the use of belatacept at the time of transplant in three EBV-seropositive adolescents in the setting of induction with alemtuzumab and methylprednisone, and it found 100% adherence and no de novo donorspecific antibody formation. 125…”
Section: Dosing and Side Effectsmentioning
confidence: 99%
“…Additional abstracts have been published describing belatacept conversion in six pediatric/AYA KTRs for CNI or mTORi toxicity 138 and in 10 pediatric/AYA KTRs for CNI minimization early posttransplant or withdrawal for CNI toxicity 139 . The most recent publication of belatacept use in adolescent kidney transplantation described patient‐tailored use of belatacept in three patients utilizing a steroid‐free belatacept and sirolimus maintenance regimen with alemtuzumab induction 140 . Conversion from a CNI‐based regimen to a belatacept‐based regimen in adult KTRs has been described by several groups showing improvement in renal function postconversion 141,142 ; such positive results suggest belatacept may be a desirable alternative maintenance agent for adolescent KTRs who would benefit from CNI withdrawal or close medication monitoring during monthly i.v.…”
Section: Maintenance Immunosuppression In Pediatric Kidney Transplantmentioning
confidence: 99%
“…Depletional induction therapy 7 or prolonged use of tacrolimus with gradual wean 8 can reduce the incidence of these rejection episodes. Belatacept‐based therapies in children, albeit limited to case series, 9,10 have demonstrated stabilization in allograft function and utility in the setting of nonadherence. Unfortunately, there is a lack of large pediatric pharmacokinetic studies or trials examining the long‐term risks and benefits of belatacept in children.…”
Section: Figurementioning
confidence: 99%